2014
DOI: 10.1016/j.euroneuro.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

BDNF plasma levels after antidepressant treatment with sertraline and transcranial direct current stimulation: Results from a factorial, randomized, sham-controlled trial

Abstract: Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation intervention that modifies cortical excitability according to the stimulation parameters. Preclinical and clinical studies in healthy volunteers suggest that tDCS induces neuroplastic alterations of cortical excitability, which might explain its clinical effects in major depressive disorder (MDD). We therefore examined whether tDCS, as compared to the antidepressant sertraline, increases plasma brain-derived neurotrophic factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
3
33
1
1
Order By: Relevance
“…Our results are in agreement with reports showing increased plasma BDNF in depressed patients treated with SSRIs such as sertraline (Brunoni et al 2014),…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in agreement with reports showing increased plasma BDNF in depressed patients treated with SSRIs such as sertraline (Brunoni et al 2014),…”
supporting
confidence: 83%
“…There is evidence that both serum and plasma BDNF concentrations are decreased in patients with MDD (Piccinni et al 2008) and antidepressants are reported to normalize these abnormalities (Aydemir et al 2006;Piccinni et al 2008;Sen et al 2008). Some research supports ((Sen et al 2008) the use of increased peripheral levels of BDNF as a screening tool for novel antidepressant agents, while other research opposes ( (Brunoni et al 2014;Buttenschøn et al 2015;Deuschle et al 2013;Knorr et al 2015) this proposition. Antidepressants influence both peripheral BDNF and platelet 5-HT concentrations.…”
Section: Introductionmentioning
confidence: 97%
“…While peripheral BDNF reduction during depression has often been replicated, there are open questions about the exact role of BDNF in the pathophysiology and especially in the psychopharmacological treatment of depression. Thus the results, showing that especially the reduction of BDNF must be restored to achieve antidepressant response, are questioned by contrary findings in rather recent clinical and preclinical studies [17,18,19,20,21]. So, there is even evidence that there could be a clinical response in the absence of a BDNF increase [22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 89%
“…tDCS does not seem to induce peripheral effects in cases of depression, such as changes to blood neurotrophic factors. 77,90,91 However, it increases central neuroplasticity as indexed by paired associative stimulation, 92 modulates cortical activity as indexed by electroencephalography 93 and improves working memory and affective processing. [94][95][96] Finally, since the same analyses will be performed in the escitalopram group, we will also explore whether the biological predictors and mediators are different between tDCS and escitalopram responders.…”
Section: Discussionmentioning
confidence: 99%
“…74,75 Nonetheless, recent meta-analyses showed that ECT increases BDNF levels in blood, but not rTMS or tDCS. 76,77 The possible explanations for this are the low number of rTMS/tDCS studies that used non-optimal treatment protocols and the lower period of observation between measurements. In ELECT-TDCS, BDNF levels in blood are assessed at baseline, week 3 and the endpoint.…”
Section: D) Brain Imaging By Means Of Mri Will Be Collected In Approxi-mentioning
confidence: 99%